Different risk and prognostic factors for liver metastasis of breast cancer patients with de novo and relapsed distant metastasis in a Chinese population - Zhang, Ningning; Xiang, Yimei; Shao, Qing; Wu, Jing; Liu, Yumin; Long, Hua; Tao, Dan; Zeng, Xiaohua (Frontiers in Oncology, 2023)
Purpose The present study aimed to identify clinicopathological characteristics of breast cancer liver metastasis (BCLM) as well as to characterize the risk and prognostic factors for liver metastasis (LM) of breast cancer patients with de novo and relapsed distant metastasis in a Chinese population. Materials and methods Patients with metastatic breast cancer (MBC) who were hospitalized in the Breast Cancer Center at Chongqing University between January 2011 and December 2019 were included in the present study. Logistic regression analyses were conducted to identify risk factors for the presence of BCLM. Cox proportional hazard regression models were performed to determine the prognostic factors for the survival of BCLM patients. The correlation between LM and overall survival (OS) was assessed by the Kaplan-Meier method. Results In total, 1228 eligible MBC patients, including 325 cases (26.5%) with de novo metastasis (cohort A) and 903 cases (73.5%) with relapsed metastasis (cohort B), were enrolled in the present study. In cohorts A and cohort B, 81 (24.9%) and 226 (25.0%) patients had BCLM, respectively. Patients in these two cohorts had different clinicopathological features. Logistic regression analysis identified that HER2 status in cohort A as well as HER2 status and invasive ductal carcinoma (IDC) histology in cohort B were risk factors for BCLM. The median OS of patients with LM was inferior to that of non-LM patients (17.1 vs. 37.7 months, P = 0.0004 and 47.6 vs. 84.0 months, P < 0.0001, respectively). Cox analysis identified that primary T stage, Ki67 level and breast surgery history were independent prognostic factors for cohort A and B, respectively. Conclusions De novo and relapsed MBC patients have different risk and prognostic factors for LM. Patients with BCLM have unfavorable prognosis.